Qualitative and quantitative characteristics of SenSi-1 Agrinak chicken - Hasnelly .; Sofjan Iskandar; Tike Sartika (Jurnal Ilmu Ternak dan Veteriner, 2017)
One of local chicken breeds develop in Indonesian Research Institute for Animal Production (IRIAP) is local SenSi-1 Agrinak chicken. This new improved local-meat-type breed was released with Ministry Agriculture Decree Number 39/Kpts/PK.020/1/2017 on 20th January 2017. SenSi-1 Agrinak was originally selected from native Sentul chicken breed obtained from Ciamis district in West Java Province. Selection criteria were two feather colors of grey or black spotted white (pucak), which were applied to both males and females. Pea-comb type was also one criterion for males, applied at the age of 10 weeks. Live weight at the age of 10 weeks with the selection intensity of 25% was applied to each generation of males chicken. Selection proceeded for six generations. Selection program was carried out under standard feed formulae containing around 17% crude protein with 2850 kcal ME/ kg, and containing other nutrients following the ones recommended for modern chicken of White Leghorn. Observation was conducted on each of about 2000 young chickens of grey and of Pucak SenSi-1 Agrinak both males and females age of 10 and 84 weeks. Results showed that grey SenSi-1 Agrinak chicken in total population, had: i) Grey feather color distribution of 55.51% in males, and 60.77% in females; ii) Yellow shank color of 52.51% in males, and 33.33% in females; iii) Pea type comb of 90.98% in males, and 89.23% in females; iv). Ten weeks live weight of 886.38+142.93 g/bird in males, and 739.17+ 118.87 in females. Pucak SenSi-1 Agrinak chicken in total population, had: i) Pucak feather color of 75.65% in males, and 8330% in females; ii) Yellow shank color of 51.91% in males, and 36.59% in females; iii) Pea type comb of 91.55% in males, and 92.28% in females; iv) Ten weeks live weight of 908.76+ 130.98 g/bird in males, and 750.53+ 110.56 g/bird in females. Whilst for grey SenSi-1 Agrinak male chicken after selection had live weight at 10 weeks old of 1015+107 g/bird, and for Pucak SenSi-1 Agrinak male chicken was 1051+76 g/bird. This initial performance information for those two breeds of considerably improved local chicken can be used as the base of information for SenSi-1 Agrinak breed for male line of meat type of local chicken breeding.